Analysis of transient characteristics and fault ride-through control of hybrid grid-tied converters with grid-following and grid-forming - Zhai, Baoyu; Liang, Shuchao; Xu, Zhi; Deng, Fengyi; Chen, Junru; Wu, Haiyang (Frontiers in Energy Research, 2025)
When the Grid-Following (GFL) and the Grid-Forming (GFM) converters are hybrid-connected to the grid, they are coupled through the grid impedance. During grid faults, the transient characteristics of the two converters become more complex due to this coupling. If one of the converters experiences stability issues, it affects the other, making fault ride-through challenging. A mathematical model for the hybrid grid-connected system of the two converters is first established to analyze the existence conditions of the equilibrium point. Using the phase-plane method, the mutual influence mechanism during faults is revealed. Subsequently, a method to adjust the GFM phase angle based on the degree of voltage sag is proposed, which also improves the phase-locked loop (PLL) of the GFL. The influence of GFL current injection is considered to limit the GFM fault current, thereby achieving hybrid fault ride-through control. Finally, the simulation verifies the effectiveness of the proposed control strategy. The results show that the proposed method can adjust the phase angle to support the grid, ensuring that the GFM outputs more reactive current within the maximum allowable current range. Meanwhile, the GFL injects current according to grid guidelines, effectively preventing overcurrent and phase angle instability of the converters.